THE EFFECT OF TRAINING EDUCATION, CAREER DEVELOPMENT, WORK FACILITIES ON JOB SATISFACTION WITH ORGANIZATIONAL COMMITMENT AS INTERVENING VARIABLES AT PT MITRA ENERGI BATAM - M Rajagukguk, Juanroy; Wibisono, Chablullah; Satriawan, Bambang; Gita Indrawan, M.; Khaddafi, Muammar (CV. Radja Publika, 2022)
This study aims to analyzethe effect of education, training, career development, work facilities on job satisfaction with organizational commitment as an intervening variable at PT Mitra Energi Batam. The research method uses a quantitative approach with a causal design. The population of this research is all employees at PT Mitra Energi Batam with a total of 104 people. The sampling technique is total sampling so that the 104 members of the population are used as research samples. Data collection techniques using questionnaires and documentation. Data analysis using SEM analysis with PLS. The direct effect of the variable X3 Work Facilities on the variable Y Job Satisfaction has a path coefficient of 3.789 (positive), then the increase in the value of the variable X3 Work Facilities will be followed by an increase in the variable Y Job Satisfaction. (6) The direct effect of the variable X3 Work Facilities on the variable Z Organizational Commitment has a path coefficient of 2.416 (positive), then the increase in the value of the variable X3 Work Facilities will be followed by an increase in the variable Z of Organizational Commitment. (7) The direct effect of the variable Z Organizational Commitment on the Y variable Job Satisfaction has a path coefficient of 2.279 (positive), then the increase in the value of the Z variable Organizational Commitment will be followed by an increase in the Y variable Job Satisfaction. (8). The indirect effect of X1 Education and Training on the Y variable Job Satisfaction with Z Organizational Commitment as the intervening variable has a path coefficient of 1.850 (positive). (9) The indirect effect of X2 Career Development on the Y variable Job Satisfaction with Z Organizational Commitment as the intervening variable has a path coefficient of 2.147 (positive). (10) The indirect effect of X3 Work Facilities on the Y variable Job Satisfaction with Z Organizational Commitment as the intervening variable has a path coefficient of 1.511 (positive).